Percutaneous left renal vein stenting in posterior nutcracker syndrome: technical and antithrombotic nuances – a case report - Ioana-Bristena Mardare; Horia Roşianu; Adela Mihaela Șerban; Alexandra Dădârlat-Pop; Teodor Buliga; Alexandru Achim (Frontiers in Cardiovascular Medicine, 2026)
Background Posterior Nutcracker Syndrome (PNCS) is a rare variant of left renal vein (LRV) entrapment in which the compression occurs between the abdominal aorta and vertebral column. Endovascular stenting may be considered in selected patients, but technical durability and antithrombotic management remain challenging. Case summary A 64-year-old woman with chronic kidney disease and Child-Pugh A cirrhosis with portal hypertensive lesions was referred for percutaneous treatment of symptomatic PNCS. She had recurrent haematuria, left flank pain and recurrent lower urinary tract infections. Computed tomography (CT) demonstrated retroaortic LRV compression with a pre-stenotic-to-compressed segment diameter ratio of approximately 5:1 and collateral venous drainage. Dynamic renal scintigraphy showed reduced left renal uptake and invasive assessment demonstrated a 4 mmHg trans-stenotic gradient. A dedicated venous stent was deployed at the ostial LRV stenosis with limited protrusion into the inferior vena cava, achieving good expansion and no recoil. Post-procedural evolution was notable for left femoral venous access-site bleeding controlled with compression, while the LRV stent remained patent. In view of the newly implanted renal venous stent, cirrhosis-related haemostatic fragility, and early access-site bleeding, an individualized antithrombotic regimen was selected to balance stent thrombosis prevention against haemorrhagic risk, while acknowledging the current lack of standardized protocols for renal vein stenting. Discussion & conclusion This case illustrates the importance of tailoring percutaneous treatment of PNCS to both anatomy and bleeding risk. In this patient, retroaortic ostial anatomy guided the stent deployment strategy, while early access-site bleeding in the setting of cirrhosis prompted individualized antithrombotic management.